Development of problem-based learning model with metacognitive strategy to improve students’ problem-solving ability - Budi Usodo; Sutopo Sutopo; Henny Ekana C; Ira Kurniawati; Yemi Kuswardi (International Journal of Science and Applied Science: Conference Series, 2017)
This research was conducted to: examine the problem solving ability of students in mathematics education FKIP UNS, (2) develop problem-based learning model with metacognitive strategy, (3) examine the effectiveness of problem-based learning model with metacognitive strategy. Three methods were used in this research: descriptive quantitative, research and development (RnD), and experimental method. The development method used 4-D model which consists of four phases: define, design, develop, and dessimenete. Experimental method was conducted to examine the effectiveness of learning model developed. The population in this research is all students of mathematics education FKIP UNS, while the sample used is students who took the Basics Matematics course. The data collections were used in this research: test, validation sheet, and observation sheet. Descriptive quantitative analysis technique was used to analyze the instrument development. Quantitative descriptive analysis was used to describe the validators’ mark result for the learning instruments. Descriptive quantitative analysis was used to analyze the problem-solving ability test result that described by percentages. The efectiveness of model development was analyzed by T-test method. The results of this study showed that: (1) students’ problem solving ability of mathematics education FKIP UNS particularly in non-algoritmic problems is still not good, but in algoritmic problems is good enough, (2) in the development of  problem-based learning model with metacognitive strategy learning instruments, three instruments that qualify valid, practical, and effective there are:  Learning Plan, Students’ Activity Sheet, and  Students’ Teaching Material.